Novel Meandered Line EBG Filters with Significant Size Reduction Using Sine Tapering - S. M. Shakil Hassan; Kalyan Kumar Halder; Md. Nurunnabi Mollah (International Journal of Antennas and Propagation)
Tapering electromagnetic bandgap (EBG) structures is a common method in designing microstrip filters with different periodic structures. A novel technique for tapering EBG structures with the amplitude coefficients obtained from the sine function has been illustrated. This method deduces mellifluous coefficients that improves the performance with reasonable stopband width, preferable insertion loss level, and much-minimized passband ripples compared to similar designs with other tapering methods (e.g., binomial distribution, Chebyshev distribution, and conventional cosine tapering). It also offers tandem use of tapered EBG structures, leading to the novel meandered transmission line tandem design that significantly reduces the length of the filter; more than 40% is possible, compared to the uniform and conventional tapered designs. Size reduction on such a large scale will benefit the designers with the limited space issues.